Determination of Accurate Position of Umbilical Venous Catheters in Premature Infants - Akar, Selahattin; Dincer, Emre; Topcuoğlu, Sevilay; Yavuz, Taner; Akay, Hatice; Gokmen, Tulin; Karatekin, Guner (American Journal of Perinatology, 2020)
Objective The aim of the study is to determine the most accurate length and position of umbilical venous catheter (UVC).Study Design This prospective study included premature infants who were admitted to the neonatal intensive care unit with inserted UVC between January 1, 2014 and December 31, 2015. The length of UVC was calculated according to the Shukla formula [(3 × birth weight + 9)/2 + 1] and the catheter was inserted under sterile conditions. After the insertion, umbilical catheter was first evaluated through chest X-ray and then with echocardiography to confirm its position. Catheters seen on the chest X-ray at the level of T9-T10 vertebrae were classified as “accurate position,” those seen above T9 vertebra as “high position,” and the catheters identified below T10 vertebra were classified as “low position.”Results A total of 68 infants smaller than 36 weeks of gestation were included in the study. In echocardiographic evaluation, 80% of the cases identified as in the “accurate position,” 100% of the cases classified as in a “high position,” and 33% of the cases defined as in a “low position” on the chest X-rays were found to be intracardiac. In our study, length of the catheter calculated according to the Shukla formula was intracardiac in 88.2% of premature infants.Conclusion Radiography alone is not sufficient for the determination of adequate position of umbilical catheter, especially in premature infants. Specialists practicing in neonatal intensive care units could improve themselves and evaluate UVC with echocardiography, making this a routine part of clinical practice. Echocardiography-guided fixation of the catheter will reduce the complications related to catheter malposition.Key Points
Keywords: premature; umbilical catheter; accurate length; echocardiography